(untitled) (Bangladesh Journal of Medical Biochemistry, 2019)
Self-Monitoring Blood Glucose (SMBG) Devices are now thought to be an integral component in the prevention and management of diabetes mellitus which is increasingly becoming a major health and economic burden particularly in developing countries. The marketing of these Devices, however, are still not well regulated in most of the countries and this, in turn, may lead to more harm than good to the patients who are using these devices. Retailers are the most important contact points who create the interface among the Manufacturers, Professionals and Consumers for popularization of health related devices. In this study, the Users’ Choice of SMBG Devices and its determinants, as reflected in the views of the Sales Persons (in a retail shop) in Dhaka City of Bangladesh, have been explored. Twenty Sales Persons from 20 Retail Shops, purposively selected from among major Dhaka City markets where these devices are commonly sold, were individually interviewed using a pretested Interviewer administered Questionnaire. The instrument consisted of six questions covering the Users’ preference regarding quality vs cost and also regarding the guidance and motives for purchasing specific items. The results were analyzed by descriptive statistics. It was found that 90% of the consumers are dependent on the suggestions of the Sales Persons regarding the choice of devices. In 80% of the subjects the cost of the System was found to be the determining factor regarding the choice of a meter. Only among 20% subjects, quality played any role in the choice. In conclusion, the choice of specific SMBG devices in Dhaka City is overwhelmingly influenced by Retailers (who, in most cases are not even qualified Pharmacists or Pharmacy Assistants) and, except in few cases; Users are not concerned with quality. Price, particularly the price of the strip, is the dominant factor on Users’ choice of SMBG Devices. Bangladesh J Med Biochem 2018; 11(1): 17-21